Motivational Factors Underlying Problem Solving: Comparing Wolf and Dog Puppies' Explorative and Neophobic Behaviors at 5, 6, and 8 Weeks of Age - Marshall-Pescini, Sarah; Virányi, Zsófia; Kubinyi, Enikő; Range, Friederike (Frontiers in Psychology, 2017)
Background. Wolves have been shown to be better in independent problem-solving tasks than dogs, however it is unclear whether cognitive or motivational factors underlie such differences. In a number of species problem solving has been linked to both persistence in exploration and neophobia, suggesting both these aspects may underlie dog-wolf differences in problem solving. Indeed adult wolves have been shown to be more likely to approach a novel object and more persistent in their investigation of it, but also slower in making contact with it and more fearful of it than dogs. Methods. In the current study we investigated potential differences in equally-raised dogs’ and wolves’ explorative and neophobic behaviours in a novel environment and with novel objects at 5, 6 and 8 weeks of age. Results. Results showed that wolves were more persistent in exploring both the environment and the objects than dogs, and this was the case at all ages. There were no differences in the frequency of fear-related behaviours and time spent in proximity to humans. Stress-related behaviours were similarly expressed at 5 and 6 weeks, although wolves showed a higher frequency of such behaviours at 8 weeks. Discussion. Overall, results with puppies confirm those with adult animals: wolves appear to be more explorative than dogs. Such motivational differences need to be taken into account when comparing dogs and wolves in cognitive tasks.